Cover Picture: Alcohol Dimer is Requisite to Form an Alkyl Oxonium Ion in the Proton Transfer of a Strong (Photo)Acid to Alcohol (Chem. Eur. J. 13/2016). Issue 13 (26th February 2016) - Park, Sun‐Young; Lee, Young Min; Kwac, Kijeong; Jung, Yousung; Kwon, Oh‐Hoon
Abstract : The formation of an alkyl oxonium ion, which has long been proposed as a key reaction intermediate in alcohol dehydration, is studied by time‐resolved fluorescence quenching of a strong photoacid. It is revealed for the first time that the collaboration of two alcohol molecules through hydrogen bonding is critical to enhancing their reactivity and promotes the resulting alcohol cluster to form a Brønsted base when reacting with an acid as strong as sulfuric acid. This finding addresses, as in water, the cooperative role of protic solvent molecules to facilitate nonaqueous acid–base reactions. More information can be found in the Communication by Y. Jung, O. H. Kwon et al. onpage 4340 ff.